Plan estratégico de capacitacion aplicada al personal administrativo del gobierno autonomo descentralizado municipal del canton Pichincha, provincia de Manabi, para el año 2012. - Navia Zambrano, Luis Gabriel (2011)
This research seeks to identify the main problems that exists within the care they provide administrative employees of the Autonomous Decentralized Pichincha Canton Municipal, due to the continuing lack of training in the different administrative areas identified. During the investigation, was evident observing the discomfort of the citizens who complain, care provided by office employees. They are dissatisfied with the quality of service provided and even consider it regular. This research is the outcome of an intensive field survey was to direct the public feeling and the reality they have to spend a day each time they visit the facilities of the Autonomous Decentralized Canton Municipal Pichincha, just as is administrative employees surveyed who work in the institution and to know how they were selected to enter work and training they receive in their jobs, were held with the head of the department of human talent Mr. Antonio Ormaza, mechanisms and strategies used to achieve our objective were: The study was based on deductive methods, analytical and statistical. Also using the statistical method consisted of a systematic and organized process was aimed porcentuar, tabular and graph and then analyze and interpret the results related to the different parts of the investigation. Regarding the population was taken as reference to the inhabitants of the canton of Pichincha which is considering the 33,571 inhabitants 20% of the economically active population, which is surveying the universe of 378 people. According to the analysis of the surveys was the need to raise a model strategic training plan and that citizens are dissatisfied by the service provided and 100% of administrative staff considered the need for training on issues concerning their areas of work, customer service, human relations and in this way contribute to the institutional development of the municipality. From here arises the question for our research, the development of a strategic training plan will determine the areas to be trained in the Autonomous Government of the Canton Municipal Decentralized Pichincha. Finally a review of the most relevant literature and corporate websites of the various players that allowed us to establish the theoretical foundations to explain the conceptualizations used in this research.